Production of Particleboards from Hevea brasiliensis Clones and Castor Oil-based Polyurethane Resin - Gava, Maristela [UNESP]; Muezel, Sarah D. [UNESP]; Lima, Larissa R. de [UNESP]; Cortez-Barbosa, Juliana [UNESP]; Garcia, Jose N.; Ferreira, Bruno S. [UNESP]; Servolo Filho, Henrique J.; Bernardes, Marcos S.; De Araujo, Victor A. (North Carolina State Univ Dept Wood & Paper Sci, 2015)
The economic exploitation of rubber tree (Hevea brasiliensis) usage is primarily directed toward latex extraction. After the productive life of the rubber tree forest, the managed area is harvested for planting reformulation. The harvested wood is most often used for energy generation purposes. The aim of this work was to study the feasibility of using rubberwood waste and castor oil-based polyurethane resin in the production of particleboards. Homogeneous and heterogeneous panels were made with nominal dimensions of 500 x 500 mm and thicknesses of 10 mm using particles from GT1 and RRIM600 clones of the rubber tree and 12% castor oil-based polyurethane adhesive. The panels were pressed at 140 degrees C for 12 min with 40 kgf/cm(2) specific pressure. Density, moisture content, thickness swelling, water absorption for 2 and 24 h, static bending, and internal bonding determinations were performed according to the Brazilian Standard (NBR) 14810-3 (2006) for the physical-mechanical panel characterization. The results show that using Hevea brasiliensis in particleboard production is viable. However, multilayer boards exhibited better results.
Keywords: Physical-mechanical properties; Wooden-based material; Rubber tree; Waste use